Answer:
x = 3 and y = 2
or
(3,2)
Step-by-step explanation:
first equation (LCM = 3 x 4 x 5 = 60)
(x+2)/5 - (9-x)/3 = (y - 6)/4
12(x+2) - 20(9-x) = 15(y - 6)
12x + 24 - 180 + 20x = 15y - 90
32x - 15y = -90 - 24 + 180
32x - 15y = 66
second equation:
8(x + 2) - (2x + y) = 2(x + 13)
8x + 16 - 2x - y = 2x + 26
6x - y + 16 = 2x + 26
4x - y = 10
Now you have 2 equations:
4x - y = 10 ---> y = 4x - 10
32x - 15y = 66
Substitute y = 4x - 10 into 32x - 15y = 66
32x - 15(4x - 10) = 66
32x - 60x + 150 = 66
-28x = -84
x = 3
y = 4(3) - 10
y = 12 - 10
y = 2
Solutions: x = 3 and y = 2
Answer:
$32,400
Step-by-step explanation:
We can just replace 12 for x in the equation y = 2700x
y = 2700x
y = 2700(12)
y = 32,400
The money paid after 12 years is $32,400
-Chetan K
Answer:
is it a test and what is the lesson name called?
Step-by-step explanation:
Is this what are you looking for??
C is right. She has partially completed the construction. Her next step is to use the arc markings to determine the radius to construct the circle.